1978
DOI: 10.2136/sssaj1978.03615995004200060007x
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Dimensionless Phosphate Adsorption Isotherm for Soil

Abstract: A unique dimensionless phosphate adsorption isotherm, covering the solution concentration range 10−6 to 10−1M P, which has been found to fit 17 materials including 15 soils, pure kaolinite and amorphous Al(OH)3, is derived. The soils shown to fit the isotherm include chromic luvisols, pellic vertisols, calcic luvisols, a tropeptic eutrorthox, a volcanic ash soil from New Zealand, and a number of English soils.The necessary parameters to derive, a complete adsorption isotherm for a particular soil, from the uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This observation further substantiates the importance of M-OH groups in the sorption of P by a wide range of soil types. Shayan and Davey (1978) have also shown that P sorption by soils, short-range order Al (OH),, and kaolinite may be described by a single dimensionless isotherm. The fact that the generalised isotherm for P sorption by soils follows the isotherms for P sorption by aluminous and short-range order Fe sorbents suggests the importance of soil components of this type in the sorption of P by soils.…”
Section: Resultsmentioning
confidence: 98%
“…This observation further substantiates the importance of M-OH groups in the sorption of P by a wide range of soil types. Shayan and Davey (1978) have also shown that P sorption by soils, short-range order Al (OH),, and kaolinite may be described by a single dimensionless isotherm. The fact that the generalised isotherm for P sorption by soils follows the isotherms for P sorption by aluminous and short-range order Fe sorbents suggests the importance of soil components of this type in the sorption of P by soils.…”
Section: Resultsmentioning
confidence: 98%
“…Although the Langmuir equation has been used to describe the relation, it seldom gives a realistic description. The relation is often closely described over limited ranges by the Freundlich equation (Barrow, ) but over larger ranges, modifications to the Freundlich equation give a better fit (Shayan & Davey, ; Sibbesen, ).…”
Section: The Observations To Be Describedmentioning
confidence: 99%
“…Although the Langmuir equation has been used to describe the relation, it seldom gives a realistic description. The relation is often closely described over limited ranges by the Freundlich equation (Barrow, 1978) but over larger ranges, modifications to the Freundlich equation give a better fit (Shayan & Davey, 1978;Sibbesen, 1981). It is often found that sorption of phosphate is decreased if the pH is increased (reviewed by Sanchez & Uehara, 1980), but the effects only become large if high pH values are used.…”
Section: The Observations To Be Describedmentioning
confidence: 99%